2021
DOI: 10.1158/2326-6066.cir-20-0405
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Triple-Negative Breast Cancer with Combination Therapy of EGFR CAR T Cells and CDK7 Inhibition

Abstract: Epidermal growth factor receptor-targeted chimeric antigen receptor T cells (EGFR CAR-T) are potent and specific in suppressing the growth of triple-negative breast cancer (TNBC) in vitro and in vivo. However, in this study, a subset of mice soon acquired resistance, which limits the potential use of EGFR CAR-T. We aimed to find a way to overcome the observed resistance.Transcriptomic analysis results revealed that EGFR CAR-T treatment induced a set of immunosuppressive genes, presumably through interferon-gam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…In a mouse model of TNBC, it has been shown that the pre-treatment with EGFR-specific CAR-T, induced the development of resistance in tumor cells. This effect could be subsequently reversed by using THZ1, an agent that inhibited the phosphorylation of cyclin-dependent kinase 7 (CDK7)-mediated RNA polymerase II and, therefore, resulted in the diminished expression of the immunosuppressive genes (e.g., CD274 (PD-L1), PDCD1LG2 (PD-L2), IDO1 ) [ 195 ]. A “headless CAR-T” consisting of intracellular activation domains armed with HER2 or EGFR bispecific antibodies showed great potential in a mono- or sequential killing manner and was able to kill in vitro under hypoxic conditions [ 196 ].…”
Section: Strategies To Overcome Immunotherapy Resistance Of Breast Cancermentioning
confidence: 99%
“…In a mouse model of TNBC, it has been shown that the pre-treatment with EGFR-specific CAR-T, induced the development of resistance in tumor cells. This effect could be subsequently reversed by using THZ1, an agent that inhibited the phosphorylation of cyclin-dependent kinase 7 (CDK7)-mediated RNA polymerase II and, therefore, resulted in the diminished expression of the immunosuppressive genes (e.g., CD274 (PD-L1), PDCD1LG2 (PD-L2), IDO1 ) [ 195 ]. A “headless CAR-T” consisting of intracellular activation domains armed with HER2 or EGFR bispecific antibodies showed great potential in a mono- or sequential killing manner and was able to kill in vitro under hypoxic conditions [ 196 ].…”
Section: Strategies To Overcome Immunotherapy Resistance Of Breast Cancermentioning
confidence: 99%
“…Transcriptomic analysis of mice bearing a triple-negative breast cancer with an acquired resistance to anti-EGFR CAR T cells showed that treatment with EGFR-specific CAR T cells induced immunosuppressive genes that were associated with CAR T cell-activated enhancers [ 112 ]. Screening a panel of epigenetic modulators revealed that these enhancers were sensitive to the selective and potent covalent cyclin-dependent kinase 7 (CDK7) inhibitor THZ1.…”
Section: Synergistic Combination Therapy With Car T Cellsmentioning
confidence: 99%
“…Screening a panel of epigenetic modulators revealed that these enhancers were sensitive to the selective and potent covalent cyclin-dependent kinase 7 (CDK7) inhibitor THZ1. As THZ1 can suppress anti-EGFR CAR T cell-induced immunosuppressive genes, the combination of THZ1 with CAR T cells was investigated, revealing an enhanced in vitro efficacy compared to anti-EGFR CAR T cells or THZ1 alone [ 112 ]. In vivo combination therapy of EGFR-specific CAR T cells with the CDK7 inhibitor THZ1 showed a suppression of immune resistance, tumor growth, and metastasis in triple-negative breast cancer models [ 112 ].…”
Section: Synergistic Combination Therapy With Car T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative, the blockage of immune regulatory checkpoints of T cells via CRISPR/Cas9-mediated gene editing could also improve the outcome of CAR cell therapies [ 116 ]. Similarly, inhibiting immunosuppressive genes that are activated upon IFN-γ secretion by EGFR CAR T cells can improve the efficacy of targeted therapies, in vivo [ 117 ]. Ongoing efforts are attempting to apply EGFR CAR cells in clinical trials.…”
Section: Established Targets For Car Nk Cellsmentioning
confidence: 99%